The Trace Amine-Associated Receptor 1 Agonist 3-Iodothyronamine Induces Biased Signaling at the Serotonin 1b Receptor - Bräunig, Julia; Dinter, Juliane; Höfig, Carolin S.; Paisdzior, Sarah; Szczepek, Michal; Scheerer, Patrick; Rosowski, Mark; Mittag, Jens; Kleinau, Gunnar; Biebermann, Heike (Frontiers in Pharmacology, 2018)
Trace amine-associated receptors (TAARs) belong to the class A G-protein-coupled receptors (GPCR) and are evolutionary related to aminergic receptors. TAARs have been identified to mediate effects of trace amines. TAAR1 signaling is mainly mediated via activation of the Gs/adenylyl cyclase pathway. In addition to classical trace amines, TAAR1 can also be activated by the thyroid hormone derivative 3-iodothyronamine (3-T1AM). Pharmacological doses of 3-T1AM induced metabolic and anapyrexic effects, which might be centrally mediated in the hypothalamus in rodents. However, the observed anapyrexic effect of 3-T1AM persists in Taar1 knock-out mice which raises the question whether further GPCRs are potential targets for 3-T1AM and mediate the observed physiological effect. Anapyrexia has been observed to be related to action on aminergic receptors such as the serotonin receptor 1b (5-HT1b). This receptor primarily activates the Gi/o mediated pathway and PLC signaling through the Gof Gi/o. Since the expression profiles of TAAR1 and 5-HT1b overlap, we questioned whether 3-T1AM may activate 5-HT1b. Finally, we also evaluated heteromerization between these two GPCRs and tested signaling under co-expressed conditions. In this study, we showed, that 3-T1AM can induce Gi/o signaling through 5-HT1b in a concentration of 10 µM. Strikingly, at 5-HT1b the ligand 3-T1AM only activates the Gi/o mediated reduction of cAMP accumulation, but not PLC activation. Co-stimulation of 5-HT1b by both ligands did not lead to additive or synergistic signaling effects. In addition, we confirmed the capacity for heteromerization between TAAR1 and 5-HT1b. Under co-expression of TAAR1 and HTR1b, 3-T1AM action is only mediated via TAAR1 and activation of 5-HT1b is abrogated. In conclusion, we found evidence for 5-HT1b as a new receptor target for 3-T1AM, albeit with a different signaling effect than the endogenous ligand. Altogether, this indicates a complex interrelation of signaling effects between the investigated GPCRs and respective ligands.